2021
DOI: 10.1177/0192513x211042852
|View full text |Cite
|
Sign up to set email alerts
|

Family Disruption and Parenting During the COVID-19 Pandemic

Abstract: Using unique data from an economically and racially diverse sample of 448 caregivers with young children (ages 4–9 years) in Ohio, we assess multiple sources of family social and economic disruptions and their associations with parenting activities during the COVID-19 stay-at-home order. Caregivers reported extensive social and economic challenges during this time, while also increasing (on average) their time spent in play/learning activities. Time spent in discipline was less likely to increase during this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Table A2 in the online appendix further indicates only a few sociodemographic differences in parents’ likelihood to work from home in 2020: Highly educated parents, those with preschool or young schoolchildren, and parents with previous experience with WFH in 2019 were more likely to switch to WFH in 2020, whereas parents in technical and other occupations (including service and sales, machine operating, and craft workers) were less likely to work from home for large parts of their working hours. Because previous research on parenting also indicated sociodemographic differences related to parental education and children's age (e.g., Schmeer et al., 2021 ; Verweij et al., 2021 ), we used this information for the selection of control variables, which may confound associations between WFH and parenting (see below).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table A2 in the online appendix further indicates only a few sociodemographic differences in parents’ likelihood to work from home in 2020: Highly educated parents, those with preschool or young schoolchildren, and parents with previous experience with WFH in 2019 were more likely to switch to WFH in 2020, whereas parents in technical and other occupations (including service and sales, machine operating, and craft workers) were less likely to work from home for large parts of their working hours. Because previous research on parenting also indicated sociodemographic differences related to parental education and children's age (e.g., Schmeer et al., 2021 ; Verweij et al., 2021 ), we used this information for the selection of control variables, which may confound associations between WFH and parenting (see below).…”
Section: Methodsmentioning
confidence: 99%
“…We further examined significant interaction effects by calculating predictive margins and average marginal effects (AME) of WFH and gender (calculated as discrete changes from 0 to 1), which we displayed graphically as well. Lastly, we addressed sociodemographic differences in the changes in responsive and harsh parenting compared to the pre‐pandemic year because prior studies documented stronger pandemic‐related effects for certain subgroups, such as highly educated mothers and parents with young children (e.g., Schmeer et al., 2021 ; Verweij et al., 2021 ). We also conducted two sets of sensitivity analyses, which examined the relationship between WFH and Δ WFC and probed the robustness of our findings for the subgroup of partnered mothers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this sample, actual financial conditions (income per capita, financial difficulties) did not distinguish family profiles, yet anxiety about future financial security distinguished both Struggling and Distressed families from Thriving families. Prior research with more socioeconomically diverse samples has shown that pandemic-related family hardship undermined family well-being ( Gassman-Pines et al, 2020 ; Chen et al, 2021 ; Feinberg et al, 2021 ; Schmeer et al, 2021 ). As the profiles did not differ in actual financial resources, financial worry may be another stressor that permeated across the socioeconomic spectrum during this period of societal economic uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing vulnerabilities, such as pre-pandemic economic hardship, may impede a family’s ability to cope with pandemic conditions ( Prime et al, 2020 ). Less financially well-off families being more adversely affected by the pandemic and associated public health regulations accompanied with heightened parenting concerns ( Chen et al, 2021 ; Feinberg et al, 2021 ; Schmeer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%